KUALITAS PENDIDIKAN POIN 4 SDGS DITINJAU DARI PENGGUNAAN MODEL CTL TERHADAP KEMAMPUAN BERPIKIR KRITIS - Bunga Rossa Indah; Baharudin Baharudin; Ayu Reza Ningrum; Ida Fiteriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Sustainable Development Goal (SDG) 4 aims to ensure quality education by fostering 21st-century competencies, one of which is critical thinking. However, elementary school students' critical thinking skills remain relatively low because learning activities are often teacher-centered and insufficiently connected to real-life contexts. One learning model that can address this issue is Contextual Teaching and Learning (CTL). This study aimed to examine the effect of the Contextual Teaching and Learning (CTL) model on students' critical thinking skills in Science and Social Studies (IPAS) as an effort to support the achievement of SDG 4. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 50 fifth-grade students who were divided into an experimental group and a control group using a purposive sampling technique. The research procedures included administering a pre-test, implementing CTL in the experimental group while the control group received conventional instruction, and conducting a post-test to measure students' critical thinking skills. The data were analyzed using the Mann–Whitney U test. The findings indicated that the experimental group demonstrated significantly higher critical thinking skills than the control group, as evidenced by an Asymp. Sig. (2-tailed) value of < 0.001. Therefore, the CTL model is effective in improving students' critical thinking skills in IPAS learning and supports the implementation of SDG 4 on Quality Education. ABSTRAK Sustainable Development Goals (SDGs) Poin 4 bertujuan mewujudkan pendidikan berkualitas melalui pengembangan kompetensi abad ke-21, salah satunya kemampuan berpikir kritis. Namun, kemampuan berpikir kritis siswa sekolah dasar masih rendah karena pembelajaran cenderung berpusat pada guru dan belum mengaitkan materi dengan konteks kehidupan nyata. Salah satu model pembelajaran yang dapat diterapkan untuk mengatasi permasalahan tersebut adalah Contextual Teaching and Learning (CTL). Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model CTL terhadap kemampuan berpikir kritis siswa pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) sebagai upaya mendukung pencapaian SDGs Poin 4. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi experiment dan desain Nonequivalent Control Group Design. Sampel penelitian berjumlah 50 siswa kelas V yang dibagi menjadi kelas eksperimen dan kelas kontrol menggunakan teknik purposive sampling. Tahapan penelitian meliputi pemberian pretest, pelaksanaan pembelajaran menggunakan model CTL pada kelas eksperimen dan pembelajaran konvensional pada kelas kontrol, serta pemberian posttest. Data dianalisis menggunakan uji Mann–Whitney U. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis siswa pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol dengan nilai Asymp. Sig. (2-tailed) < 0,001. Dengan demikian, model CTL efektif meningkatkan kemampuan berpikir kritis siswa pada pembelajaran IPAS dan mendukung terwujudnya pendidikan berkualitas sesuai SDGs Poin 4.